Faktor – Faktor Yang Berhubungan dengan Motivasi Kerja Perawat Rawat Inap Rsud Kota Tanjungpinang - Susilawati Yuliana; Rachmawaty M. Noer; Mira Agusthia (PPNI UNIMMAN, 2024)
Work motivation is the desire or desire that influences nurses' behavior in order to improve performance. There are several factors related to the work motivation of inpatient nurses at Tanjungpinang City Regional Hospital, namely responsibility, recognition, achievement, working environment conditions, interpersonal relationships and supervision. This research was conducted in the inpatient room of Tanjungpinang City Hospital, Riau Islands Province. The type of research used is quantitative research with a cross sectional approach. The population in this study were all inpatient nurses at the Tanjungpinang City Regional Hospital, namely 85 people and the number of samples in this study was 85 respondents using a total sampling technique. The statistical test used is the chi square test. The results of the research show that what influences work motivation are: Responsibility 98.87 Recognition 80.7 Achievement 83.59 Work environment conditions 51.87 Interpersonal relationships 97.64 Supervision 89.49. The results of statistical tests formulate a relationship between motivation and: Responsibility, the P value is 0.353. Achievement of P value recognition P value 0.028. Interpersonal relationships P value 0.547. Working environmental conditions P value 0.521. Supervision P value 0.334. It is hoped that the results of this research can increase the work motivation of nurses at the Tanjungpinang City Hospital.